The effect of lighting and color elements in highlighting the functional and aesthetic values of the interior spaces in the home - In'am Ahmed Abed Shuaibi (الاكاديمي)
Lighting is an important and effective element in architecture, and the reason for the individual's interaction with space and mass. Lighting design is a mixture of science and art. It is a design, creative and artistic process to highlight the aesthetic and functional values in architecture.